Pengembangan Inovasi Produk dan Digital Marketing Pada UMKM Enye Singkong Dua Putra Desa Bojong - Palahudin, Palahudin; Samsuri, Samsuri; Ramadian, Afzil; Nurdiana, Ratna Putri; Hamdani, Muhammad Fadli; Halimatussadiah, Siti; Nadifah, Najla Virda; Robyanshyah, Robyanshyah (Universitas Pahlawan Tuanku Tambusai, 2025)
Enye Singkong Dua Putra MSMEs in Bojong Village is an example of a small business that continues to strive to maintain its presence in the market by relying on its main product, processed cassava. According to the survey results, this MSMEs has the opportunity to innovate its products, but the product logo is outdated, the information system has not been optimized, and an online marketing system has not been implemented. Developing product innovation and digital marketing has become one of the Community Service (PKM) programs in Bojong Village. The purpose of the program is to provide ideas for the development of MSMEs and to help offer insights to business owners regarding the application of digital marketing. The Community service was carried out through a series of stages, starting with the survey stage, problem analysis stage, planning stage, and implementation stage. The results include innovation by adding lime leaves as a substitute for green onions and introducing new flavor variants, updating the logo to be more relevant, using Google Maps location points, creating banners, and providing digital marketing assistance on the Shopee e-commerce platform. The implementation of this program is expected to enhance competitiveness and market segmentation of these MSMEs which are becoming an increasingly digital and dynamic.